X as a proxy for tackle safety culture? Sentiment analysis of social media posts on red-carded and yellow-carded tackles during the 2019 Rugby World Cup - Ben Jones; Sharief Hendricks; Ross Tucker; Firdows Alexander (BMJ Open Sport & Exercise Medicine, 2023)
Objectives This study analysed the overall sentiment of attitudes, opinions, views and emotions expressed in posts on X related to red-carded and yellow-carded tackles during the 2019 Rugby World Cup (RWC).Methods Sentiment analysis was conducted on posts on X about red or yellow cards issued at the 2019 RWC. Posts were classified as ‘agree’, ‘disagree’ and ‘neutral’. The frequency of posts, red cards, yellow cards, all injuries, tackle injuries and total number of tackles per match were also synced to the 45-match playing schedule.Results Five tackle-related red cards were issued during the 2019 RWC, and 15 tackle-related yellow cards, with 337 and 302 posts identified for each card decision, respectively. For red cards, 42% of posts (n=158/377) agreed with the referee’s decision, 19% (n=71/377) disagreed and 40% were neutral. For yellow cards, 24% (n=73/302) agreed with the referee’s decision, 33% (n=99/302) disagreed and 43% were neutral.Conclusions For red cards, posts were 2.2 times more likely to agree with the referee’s decision than disagree. Posts that agreed with a red card decision were also more likely to be shared (reposted) than posts that disagreed with a red card decision. In contrast, sentiments expressed for yellow card decisions were mixed. This may be related to interpreting the degree of danger and whether mitigation is applied. Within the ecosystem of rugby, sharing sentiments on social media plays a powerful role in creating a positive player welfare narrative.